Assessing quality of older persons' emergency transitions between long-term and acute care settings: a proof-of-concept study. Issue 1 (9th March 2022) - Tate, Kaitlyn; McLane, Patrick; Reid, Colin; Rowe, Brian H; Cummings, Garnet; Estabrooks, Carole A; Cummings, Greta
Abstract : Background: Long-term care (LTC) residents frequently experience transitions in the location of more advanced care delivery, including receiving emergency department (ED) care. In this proof-of-concept study, we aimed to determine if we could identify measures in quality of care across transitions from LTC to the ED, via emergency medical services and back, by applying Institute of Medicine (IOM) Quality of Care Domains to an existing dataset. Methods: In the Older Persons' Transitions in Care (OPTIC) study, we collected information on residents' transitions in two Western Canadian cities. We applied the IOM's Quality of Care Domains to the OPTIC data to create binary measures of transition quality. We report the median (MED) per cent and IQR of measures met within each domain of quality. Results: We tracked 637 transitions over a 12-month period, with data collected from each setting. We developed 19 safety measures, 20 measures of resident-centred care, 3 measures of timely care and 5 measures of effective care. We were unable to develop measures for equitable care at an individual transfer level. Domain scores varied across individual transitions, with the highest scores in safety (MED 79%, IQR: 63–95), efficiency (66%; IQR: 66–99), and resident-centred (45%; IQR: 25–65), followed by effectiveness (36%; IQR: 16–56), and timeliness (0%; IQR: 0–50). Conclusions: Our results show variation in scores across the domains of quality suggesting that it is possible to track quality of transitions for individuals across all settings, and not only within settings. We recommend that future work in tracking quality of care be performed at several levels (LTC, region, health authority, province). Such tracking is necessary to evaluate and improve overall quality of care.